1973
DOI: 10.1246/bcsj.46.1638
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of Water in Macromolecular Gels. VI. The Relationship between the Rheological Properties and the States of Water in Macromolecular Gels

Abstract: The relationship between the rheological properties and the states of water in macromolecular gels is investigated by both the rheological and nuclear magnetic resonance methods. In accordance with the stress-strain curve, macromolecular gels are shown to be classifiable into: (1) an agarose type of gel which shows great gel strength and brittleness at breaking; (2) a κ-carrageenan type of gel showing great gel strength, but ductility at breaking, and (3) a λ-carrageenan type of gel, which has very little gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, if the pore size is small enough, there is a possibility that a higher supersaturation is needed, due to the compartmentalization of solvents. Finally, this may also represent an effect in the diffusion of substances [69][70][71].…”
Section: Properties Of Gels Used For Crystallizationmentioning
confidence: 99%
“…However, if the pore size is small enough, there is a possibility that a higher supersaturation is needed, due to the compartmentalization of solvents. Finally, this may also represent an effect in the diffusion of substances [69][70][71].…”
Section: Properties Of Gels Used For Crystallizationmentioning
confidence: 99%
“…It was suggested that the gel contained junction zones of various strength and that the stronger junction zones are responsible for the equilibrium stress and the high elastic recovery. Aizawa et al (1973) have suggested that there is a correlation between the rheological properties of polysaccharide gels and the state of water in the gel as determined by NMR. The stress-strain curves obtained by these workers for agarose, lambda-carrageenan, kappa-carrageenan and the bacterial polysaccharide curdlan are shown in Figure 2.…”
Section: The Red Seaweed Polysaccharidesmentioning
confidence: 99%